IMPACT OF STATUTORY RETIREMENT AGE ON YOUTH UNEMPLOYMENT IN KWARA STATE, NIGERIA - Isiaka, Sulu Babaita; WOLI-JIMOH, Ibrahim Ayodeji (Archives of Business Research, 2017)
Youth unemployment is a pressing problem in both the advanced and developing countries of this world of which Nigeria is not an exception. More worrisome is the few research works linking Statutory Retirement Age (SRA) to youth unemployment. However, to add to the growing concern on the subject matter, the current study empirically examines the impact of statutory retirement age on youth unemployment rate in Kwara State. The study used simple random sampling technique to select a sample size of 390 civil servants from Kwara State Civil Service Commission (KWCSC). It also interviewed a focus group of graduates undergoing the One-Year program of the Kwara Bridge Empowerment Scheme (KWABES). Data obtained were presented using both descriptive and inferential statistics of simple percentage. Regression Analytical tool was used to test the hypotheses formulated for the study. The results indicate that the variability changes in the rate of youth unemployment could be accounted for by approximately 84.3% of increase in statutory retirement age. Also, the variability changes in the level of job creation opportunities could be accounted for by approximately 63.2% of factors related to statutory retirement age This established that increase in statutory retirement age have effect of increasing youth unemployment and the level of job creation depends on factors that are related to SRA. Base on this conclusions, it was recommended that the KWCSC should focus on strict implementation of SRA policies and Programmes and by this, the state government can deal decisively with the problems of youth unemployment through the Statutory Retirement Age. Keywords: Statutory, Retirement, Youth, unemployment, Kwara, Nigeria